Perception of Words and Pitch Patterns in Song and Speech - Merrill, Julia; Sammler, Daniela; Bangert, Marc; Goldhahn, Dirk; Lohmann, Gabriele; Turner, Robert; Friederici, Angela D. (Frontiers in Psychology, 2012)
This functional magnetic resonance imaging study examines shared and distinct cortical areas involved in the auditory perception of song and speech at the level of their underlying constituents: words and pitch patterns. Univariate and multivariate analyses were performed to isolate the neural correlates of the word- and pitch-based discrimination between song and speech, corrected for rhythmic differences in both. Therefore, six conditions, arranged in a subtractive hierarchy were created: sung sentences including words, pitch and rhythm; hummed speech prosody and song melody containing only pitch patterns and rhythm; and as a control the pure musical or speech rhythm. Systematic contrasts between these balanced conditions following their hierarchical organization showed a great overlap between song and speech at all levels in the bilateral temporal lobe, but suggested a differential role of the inferior frontal gyrus (IFG) and intraparietal sulcus (IPS) in processing song and speech. While the left IFG coded for spoken words and showed predominance over the right IFG in prosodic pitch processing, an opposite lateralization was found for pitch in song. The IPS showed sensitivity to discrete pitch relations in song as opposed to the gliding pitch in speech. Finally, the superior temporal gyrus and premotor cortex coded for general differences between words and pitch patterns, irrespective of whether they were sung or spoken. Thus, song and speech share many features which are reflected in a fundamental similarity of brain areas involved in their perception. However, fine-grained acoustic differences on word and pitch level are reflected in the IPS and the lateralized activity of the IFG.